Imbalance of Circulating Innate Lymphoid Cell Subpopulations in Patients With Septic Shock - Carvelli, Julien; Piperoglou, Christelle; Bourenne, Jeremy; Farnarier, Catherine; Banzet, Nathalie; Demerlé, Clemence; Gainnier, Marc; Vély, Frédéric (Frontiers in Immunology, 2019)
ABSTRACT Background Septic shock, a major cause of death in critical care, is the clinical translation of a cytokine storm in response to infection. It can be complicated by sepsis-induced immunosuppression, exemplified by blood lymphopenia, an excess of circulating Treg lymphocytes, and decreased HLA-DR expression on circulating monocytes. Such immunosuppression is associated with secondary infections and higher mortality. The effect of these biological modifications on circulating innate lymphoid cells (ILCs) has been little studied. Methods We prospectively enrolled patients with septic shock (Sepsis-3 definition) in the intensive care unit (ICU) of Timone CHU Hospital. ICU controls (trauma, cardiac arrest, neurological dysfunction) were recruited at the same time (NCT03297203). We performed immunophenotyping of adaptive lymphocytes (CD3+ T cells, CD19+ B cells, CD4+CD25+FoxP3+ Treg lymphocytes), ILCs (CD3-CD56+ NK cells and helper ILCs – ILC1, ILC2, and ILC3), and monocytes by flow cytometry on fresh blood samples collected between 24 and 72 hours after admission. Results We investigated adaptive and innate circulating lymphoid cells in the peripheral blood of 18 patients in septic shock, 15 ICU controls, and 30 healthy subjects. As expected, the peripheral blood lymphocytes of all ICU patients showed lymphopenia, which was not specific to sepsis, whereas those of the healthy volunteers did not. Circulating CD3+ T cells and CD3-CD56+ NK cells were mainly concerned. There was a tendency towards fewer Treg lymphocytes and lower HLA-DR expression on monocytes in ICU patients with sepsis. Although the ILC1 count was higher in septic patients than healthy subjects, ILC2 and ILC3 counts were lower in both ICU groups. However, ILC3s within the total ILCs were overrepresented in patients with septic shock. The depression of immune responses has been correlated with the occurrence of secondary infections. We did not find any differences in ILC distribution according to this criterion. Conclusion All ICU patients exhibit lymphopenia, regardless of the nature (septic or sterile) of the initial medical condition. Specific distribution of circulating ILCs, with an excess of ILC1 and a lack of ILC3, may characterize septic shock during the first three days of the disease.